Samoa Gender and Investment Climate Reform Assessment - Hedditch, Sonali (International Finance Corporation, Washington, DC, 2017)
This report is one of six gender and investment climate reform assessments undertaken in six Pacific nations including Samoa. The report analyses gender-based investment climate barriers which constrain private sector development and identifies solutions to address them. Six investment climate areas are considered: public private dialogue; starting and licensing a business; access to justice and alternative dispute resolution; access to, and enforcement of, rights over registered land; access to finance; and access to, and enforcement of, rights over intellectual property. In each area the report considers legal, regulatory, and administrative barriers to private sector development with a gender perspective. It makes recommendations aimed at ensuring that women benefit from ongoing efforts to improve Samoa’s investment climate on the same basis as their male counterparts. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.